2D Z-scheme heterojunction and oxygen deficiency synergistically boosting the photocatalytic activity of a layered BaTiO3/BiOIO3 composite. (December 2022) - Jing, Panpan; He, Chenpu; Huang, Shengchi; Li, Haohui; Liu, Jiale; Cui, Yongfei; Pu, Yongping; Wang, Jenghan
Highlights: A layered BaTiO3 /BiOIO3 composite was constructed via a versatile hydrothermal method. The BaTiO3 /BiOIO3 composite exhibited an outstanding photo response, separation efficiency and high redox capability of photo-excited carriers due to the synergistic effect of rich oxygen deficiency and 2D Z-scheme heterojunction with IO3 − /I − redox pairs. The IO3 − /I − redox pair and coupled band gap of the BaTiO3 /BiOIO3 composite were highly related to oxygen deficiency. The BaTiO3 /BiOIO3 composite performed an ultrahigh catalytic activity toward to the photo-degradation of tetracycline and rhodamine B. Abstract: Simultaneously enhancing the quantity, separation efficiency and redox capability of photo-excited carriers to boost the catalytic activity has always been the toughest challenge for a photocatalyst. Herein, we presented a novel BaTiO3 /BiOIO3 layered composite by proposing a synergistic strategy of 2D Z-scheme heterojunction and rich oxygen deficiency. Due to the high-quality interfaces with strong coupling interaction and stable IO3 − /I − redox pairs between BaTiO3 and BiOIO3 layers, the composite was endowed concurrently with the strengthened photo response, separation efficiency and high redox capability of photo-excited carriers through a Z-scheme migration pathway. DFT computation emphasized that the formation of IO3 − /I − redox pair and band gap of the composite were highly related to oxygen deficiency. Moreover, the ·O2 − radicals can be expansively stimulated by the well-known local surface plasmon resonance effect of oxygen deficiency via inducing extra hot electrons. As a result, the composite performed a 4.4-fold enhanced photocatalytic activity than pure BaTiO3 toward the photo-degradation of tetracycline, which can be completed in just a few minutes. Therefore, we hope that the proposed heterojunction and oxygen deficiency synergistic boosting the photocatalytic activity of BaTiO3 could open a lot of insights for developing more efficient composite photocatalysts to solve the water pollutions. Graphic abstract: Image, graphical abstract